2017
DOI: 10.1057/s41274-016-0141-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimal contract design for cloud computing service with resource service guarantee

Abstract: The optimal contract design for cloud computing service with resource guarantee under the consideration of resource redundancy and network externality is studied in this research. A model in which a service provider determines joint pricing and resource allocation decisions is constructed by proposing two types of contracts with different service-level agreements (SLAs). The SLA of each contract describes the price and associated penalty if the provider cannot provide the resource requested by the customers. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A SLA is formulated in the cloud contract to ensure that the service level is consistent with the agreement in terms of the price, resource allocation, penalty rate, etc. (Kuo et al , 2017). In all, five papers discussed SLA.…”
Section: What Cloud Issues Can Small- and Medium-size Enterprises Foc...mentioning
confidence: 99%
See 2 more Smart Citations
“…A SLA is formulated in the cloud contract to ensure that the service level is consistent with the agreement in terms of the price, resource allocation, penalty rate, etc. (Kuo et al , 2017). In all, five papers discussed SLA.…”
Section: What Cloud Issues Can Small- and Medium-size Enterprises Foc...mentioning
confidence: 99%
“…Yigitbasioglu (2015) explored why organizations adopt or not cloud computing and found that one of the concerns for cloud adoption is the poor SLA which is derived from the ignorance of the technology(s) being used and their own requirements. Kuo et al (2017) studied the optimal cloud contract design and proposed a model of the decision of pricing and resource allocation that is constructed by different contracts with different SLA. Yuan et al (2018) addressed the resource back-up, penalty determination and penalty deferred pricing issues and found that the SLA parameters significantly interacted with resource back up.…”
Section: What Cloud Issues Can Small- and Medium-size Enterprises Foc...mentioning
confidence: 99%
See 1 more Smart Citation
“…To remove the redundancy and network externality is analyzed for the cloud service providers with resource assurance by optimal contract design in cloud computing. This model characteristic is analyzed for optimal costing and resource allocation decisions as well as made a contract of cloud service providers which shows that both service providers and service users compensation ratio is unfulfilled (11).…”
Section: Related Workmentioning
confidence: 99%
“…In their suggested contract, the relief agencies and suppliers are committed on a pre-specified amount for purchasing and supplying in the contract. Kuo et al [35] proposed a service provider model to determine mutual resource allocation and pricing decisions. They considered two types of contracts with distinct service-level agreements and focused on the optimal contract design.…”
Section: Contractsmentioning
confidence: 99%